Behavior of schmutzdecke with varied filtration rates of slow sand filter to remove total coliforms - matuzahroh, Ni’; Fitriani, Nurina; Ardiyanti, Putri Eka; Kuncoro, Eko Prasetyo; Budiyanto, Wahid Dian; Isnadina, Dwi Ratri Mitha; Wahyudianto, Febri Eko; Radin Mohamed, Radin Maya Saphira (Elsevier, 2020)
The previous research showed that slow sand filtration (SSF) can remove the total coli by approximately 99% because of the schmutzecke layer in the filter. The presented study aimed to complete the previous research on SSF, especially on the schmuztdecke layer mechanism, to remove total coli. Total coli is a parameter of water quality standard in Indonesia, and the behavior of schmutzdecke affects the total coli removal. In the present study, the raw water from Amprong River was treated using horizontal roughing filter (HRF) and SSF. The variations in SSF rate used were 0.2 and 0.4 m/h. Total coliforms were analyzed using the most probable number test, and schmutzdecke visualization was conducted through scanning electron microscopy–energy-dispersive X-ray spectroscopy (SEM–EDX). The best coliform concentration in water treated by the combination of HRF and SSF was 4,386 colonies per 100 mL of sample using the filtration rate of 0.2 m/h, and its removal efficiency was 99.60%. However, the quality of water treated by the combination of HRF and SSF did not meet the drinking water quality standard because the removal of total coli must be 100%. The SEM–EDX visualization results in schmutzdecke showed that the average bacteria in the schmutzdecke layer were small, white, opaque, and circular, with entire edge and flat elevation. The Gram test results showed that the schmutzdecke bacteria consisted of Gram-positive and Gram-negative bacteria with basil as the common cell form.